Implementasi Kebijakan Desa Dalam Mengembangkan Badan Usaha Milik Desa Di Kabupaten Klaten Provinsi Jawa Tengah - Joni Agung Priyanto (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2020)
The phenomenon used as the object of research is the implementation of Village policies in developing BUM Desa. The research objectives are: first, to analyze the implementation of village policies in developing village-owned enterprises in Klaten Regency; second, compiling a model from the results of the analysis of Village Policy Implementation in developing Village-Owned Enterprises in Klaten Regency. This research uses qualitative research. The 11 research informants were determined by purposive sampling technique and snow ball technique. Secondary data collection using literature study; Primary data collection using interview and observation techniques. The discussion of the research results used descriptive analysis which was developed by using triangulation analysis by observers.